Human Immune System Development and Rejection of Human Islet Allografts in Spontaneously Diabetic NOD-Rag1(null) IL2rγ(null) Ins2(Akita) Mice - Brehm, Michael A. (American Diabetes Association, 2010)
OBJECTIVE: To create an immunodeficient mouse model that spontaneously develops hyperglycemia to serve as a diabetic host for human islets and stem cell–derived β-cells in the absence or presence of a functional human immune system. RESEARCH DESIGN AND METHODS: We backcrossed the Ins2(Akita) mutation onto the NOD-Rag1(null) IL2rγ(null) strain and determined 1) the spontaneous development of hyperglycemia, 2) the ability of human islets, mouse islets, and dissociated mouse islet cells to restore euglycemia, 3) the generation of a human immune system following engraftment of human hematopoietic stem cells, and 4) the ability of the humanized mice to reject human islet allografts. RESULTS: We confirmed the defects in innate and adaptive immunity and the spontaneous development of hyperglycemia conferred by the IL2rγ(null), Rag1(null), and Ins2(Akita) genes in NOD-Rag1(null) IL2rγ(null) Ins2(Akita) (NRG-Akita) mice. Mouse and human islets restored NRG-Akita mice to normoglycemia. Insulin-positive cells in dissociated mouse islets, required to restore euglycemia in chemically diabetic NOD-scid IL2rγ(null) and spontaneously diabetic NRG-Akita mice, were quantified following transplantation via the intrapancreatic and subrenal routes. Engraftment of human hematopoietic stem cells in newborn NRG-Akita and NRG mice resulted in equivalent human immune system development in a normoglycemic or chronically hyperglycemic environment, with >50% of engrafted NRG-Akita mice capable of rejecting human islet allografts. CONCLUSIONS: NRG-Akita mice provide a model system for validation of the function of human islets and human adult stem cell, embryonic stem cell, or induced pluripotent stem cell–derived β-cells in the absence or presence of an alloreactive human immune system.